Simultaneous determination of methanol and ethanol in local and foreign alcoholic drinks by GC-FID - Kalid, Manja Murni Che (2022)
Intoxication with methanol resulting from the consumption of alcoholic beverages is a worldwide issue that is growing. Methanol can cause severe health issues and lead to fatality. Due to these reasons, numerous methods for measuring methanol concentrations in alcoholic beverages had been developed. The aim of this study was to develop an accurate, sensitive and simple method by using GC-FID for simultaneous determination of methanol and ethanol in local and foreign brands of alcoholic beverages. The method was developed by optimisation of the GC parameters. Optimised parameters included an initial oven temperature of 40°C held for 2 minutes, ramping at 25 °C/min until an oven temperature of 100°C was reached, a carrier gas flow rate of 4.5 mL/min, a split ratio of 2:1 with injection volume of 10 μL. The optimised method was validated in accordance with UNODC guidelines in terms of specificity, linearity, detection and quantification limits, precision and accuracy. Both methanol and ethanol calibration curves offered good linearity, with r2 > 0.99 throughout ranges of 0.001-0.625% for methanol and 5-25% for ethanol. The respective LOQs for methanol and ethanol were 1.72 mg/L and 1.76 mg/L with good precision and recoveries. This method required 5.40 minutes to yield results. This established method was then applied by analysing 19 different alcoholic beverages by injecting them directly into the GC-FID after acetonitrile was added as an internal standard. This study revealed that 36.8% of the samples examined contained methanol concentrations ranging from 0-0.0198%, whereas ethanol was present in every sample. The proposed method was sensitive, straightforward, and did not require any pre-treatment, making it suitable for routine toxicological forensic sample analysis. Importantly, trace amounts of methanol were reliably detected without interference from significantly higher concentrations of ethanol. In conclusion, this research had demonstrated that the DB ALC 1 column capillary in GC-FID with optimised parameters is very selective and highly sensitive in the simultaneous detection and measurement of methanol and ethanol in alcoholic beverages.